Islam Moderat di Masyarakat Multi Kultural: Internalisasi Nilai-nilai Islam Wasatiyah di Masyarakat Ngepet Srigading Sanden Bantul Yogyakarta - Suharsono, Suharsono; Ana Quthratun Nada; Hasan Labiqul Aqil; Muhammad Sirril Wafa (Al-Wasatiyah: Journal of Religious Moderation, 2023)
Success in internalizing religious values in society depends on several important things such as the method used, the character and qualifications of the preacher, and a supportive environment. To prove this, this research is presented, where the author will examine the efforts to internalize the values of religious moderation carried out by religious leaders in Ngepet Srigading Sanden Village, Bantul, Yogyakarta. This research is qualitative research with a descriptive-analytic type of field research. Data collection using observation, interview and documentation methods, using Miles and Huberman analysis, namely: data reduction, data presentation, and drawing conclusions or verification. The results of the research show that, in instilling wasatiyah Islamic values through two channels, namely: first, the important role of K.H Daru Kawantoro who has wasatiyah character is able to integrate the study of the taklim assembly with his various experiences when interacting or gathering with figures from across sects/faiths. Second, learning outside the mosque, the methods used are the uswah hasanah method and the direct practice method, the learning process occurs when the community takes lessons or imitates what is exemplified by community religious leaders, the learning is reflected in the activities and interactions demonstrated directly by K.H. Daru Kawantoro in the Ngepet Srigading Sanden Bantul Yogyakarta community.